Concepções de educação e de práticas docentes dos professores turismólogos de Cuiabá no estado do Mato Grosso - Monlevade, Ana Paula Bistaffa de (2011)
The education of tourism teachers and their work in private higher education institutions in Cuiabá, MT, are the objectives of this research. The study deals with teachers practices and their conceptions on education. From this field, the central question: Which conceptions of education and teaching practices do the tourism teachers have in the private institutions of Cuiabá? Then, the specific objectives. First, to search what the tourism teachers think about education versus higher education and their role in society. Second, to identify the teachers practices developed in classroom. Third, to describe the pedagogical knowledges of tourism teachers, revealed in their very practices. Fourth, to point out the tourism teachers profile, as they feel it. Finally, just as a methodological goal, to describe the tourism teachers profile in Cuiabá, MT. The theoretical foundation was built on four conceptions, according their authors respective thinkings: Higher Education in Brazil, Tourism Course and its renovation: Romanelli (1998), Cunha (2000), Ghiraldelli Jr. (1994), Andrade (2002), Oliveira (2005), Matias (2002), Barreto et al (2004), Neto and Maciel (2002); Teachers Education Basic Approaches: Pimenta and Anastasiou (2008), Pimenta (1996), Imbernón (2009), Zabalza (2004), Benedito (1995), Masetto (2003), Gaeta (2001) and Nascimento (2002); Conception of Education and Teachers Practices: Brandão (2007), Pimenta et al (2002), Tura et al (2004), Mizukami (1986 e 2002), Veiga (1992), Luckesi (1994), Shon (1992), Sacristán and Perez Gomez (1998), Tardif (2008), Pimenta (2009 e 2010) and Nóvoa (1999); Methodological Foundation: Rezende (1990), Moreira (2004), Dartigues (2003), Merleau Ponty (1971), Husserl (s/d), Panosso Neto (2005), Bogdan and Biklen (1994), Gil (2002), Gamboa (2008) and Marconi e Lakatos (2009). The research was made with ten tourism teachers from five private institutions which offer tourism graduations. It is a nonprobabilistic sample. Data were collected according to qualitative and phaenomenological approaches questionairies and interviews. The main results from the research are: the tourism teachers think education as school teaching and learning and see higher education as people training for work market. They reveal rich teaching habilities, without deeper pedagogical insights, as if they repeat in their teaching practices what they lived before, in their learning processes. They do reflect on their practice, but only focused on the classroom problems. They also revealed that a good tourism teacher is the well succeeded worker in tourism, not in education. Finally, the study showed that the tourism teachers consider their occupation and other professions as fields of work where we must prove the same professionalism.